Answer:
14.35
Step-by-step explanation:
1.65 + 12.7
It is 6 because 3x3=9 then you do the same for 2 so 6/9
Answer:
The compounded annually account will earn more interest over 10 years
Step-by-step explanation:
The rule of the simple interest is I = Prt, where
The rule of the compounded interest is A = P, where
- n is the number of periods
The interest I = A - P
∵ Each account start with $200
∴ P = 200
∵ They have an interest rate of 5%
∴ r = 5% = 5 ÷ 100 = 0.05
∵ One account earns simple interest and the other is compounded
annually
∴ n = 1 ⇒ compounded annually
∵ The time is 10 years
∴ t = 10
→ Substitute these values in the two rules above
∵ I = 200(0.05)(10)
∴ I = 100
∴ The simple interest = $100
∵ I = A - P
∵ A = 200
∴ A = 325.7789254
∵ I = 325.7789254 - 200
∴ I = 125.7789254
∴ The compounded interest = $125.7789254
∵ The simple interest is $100
∵ The compounded interest is $125.7789254
∵ $125.7789254 > $100
∴ The compounded annually account will earn more interest
over 10 years
Answer:
x = 14
y = 4
Explanation:
Ok so, just from looking at the two triangles i can tell they're congruent right triangles. I used different colors to show which sides of the triangle correspond and are equal to each other in my attatched photo.
So the side thats equal to x is the same length as the side that's equal to y+10 on the other triangle.
So we can write the equation x = y + 10.
Using this same method, the side that's equal to x + 2 is the same length as the side that's equal to 4y on the other triangle.
So, we can write the equation 4y = x + 2.
Now we have the equations you could rewrite to be in slope- intercept form so they're easier to graph. But a graphing calculator online would plot it just fine.
If you graph these two equations they'll intersect at the solution ( 14, 4 ). I'll include the graph in my images as well.
To check your answer, you can plug in x and y and see if the triangle sides end up being the same length. I did and it was correct.
4 - (0) = y
4 - 0 = 4 y = 4
4 - (1) = y
4 - 1 = 3 y = 3
4 - (2) = y
4 - 2 = 2 y = 2
4 - (3) = y
4 - 3 = 1 y = 1